Etika Diseminasi Informasi dalam Perspektif Komunikasi Islam dan Humanisme di Era Digital - Rafinita Aditia (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This research aims to find out how the ethics of life from the perspective of Islamic communication. The method used in this research is a qualitative research method with the type of library research using data sources in the form of reference books related to the ethics of life in the perspective of Islamic communication. The results showed that the ethics of a Muslim's life is very closely related to the morals possessed in carrying out life as a human being created by Allah SWT. In carrying out these ethics, it must be in line with the perspective of Islamic communication, namely the point of view of seeing a process of conveying information from one party to another, whose process must be in accordance with the teachings of existing Islamic teachings and laws. In this research, the perspective used is qaulan sadidan, qaulan balighan, qaulan maysuuran, qaulan layyinan, qaulan kariman, and qaulan ma'rufan. A Muslim must have life ethics, while some of the ethics of life include the ethics of life towards oneself, ethics in family, and ethics in society.